Exploring Community Readiness to Participate in COVID-19 Vaccination: A Study from Urban and Rural Areas of Sub-districts in Aceh, Indonesia - Husna, Cut; Salsabila, Diva; Kasih, Laras Cynthia (International Journal of Disaster Management, 2024)
Community readiness to receive the COVID-19 vaccination will determine the government's success in preventing the spread of COVID-19. Community readiness to participate in vaccination is closely related to information on vaccine ingredients (halal) and the positive and negative effects of the COVID-19 vaccine. Several factors related to the communitys readiness to participate in the COVID-19 vaccination, namely: confidence, complacency, constraints, calculation, collective responsibility, compliance, and conspiracy. The aim of this study was to identify the differences in community readiness for COVID-19 vaccination in two sub-districts in Aceh, Indonesia. A comparative study with a retrospective design was used in this study. The sampling was 200 people who had carried out the COVID-19 vaccination for two sub-districts. The samples were obtained by using a purposive sampling method. The data were collected using a standardized questionnaire, the 7C Vaccination Readiness Scale Questionnaire. The Mann-Whitney u-test revealed that, generally, the community readiness in two sub-districts to participate in COVID-19 vaccination was different (p=0.003). The sub-scales of community readiness in COVID-19 vaccination of complacency (p=0.003), constraints (p=0.000), calculation (p=0.012), and collective responsibility (p=0.000) showed significant differences. However, no difference in readiness on confidence (p=0.053), compliance (p=0.051), and conspiracy (p=0.419). The results of this study found sociodemographic factors such as religion and belief, highest education level, support systems, and information about the COVID-19 vaccination could be related to the research findings.